Bacteraemia predictive factors among general medical inpatients: a retrospective cross-sectional survey in a Japanese university hospital. Issue 7 (7th July 2016) - Fukui, Sayato; Uehara, Yuki; Fujibayashi, Kazutoshi; Takahashi, Osamu; Hisaoka, Teruhiko; Naito, Toshio
Abstract : Objectives: The precise criteria for obtaining blood cultures have not been established; they depend on the physician's judgement. We examined clinical parameters to determine predictive factors of bacteraemia and the need for blood cultures among general medical inpatients. Design: A retrospective cross-sectional survey. Setting: A Japanese university hospital. Participants: All general inpatients who had blood cultures taken from 1 January 2011 to 31 December 2012. Main Measures: Clinical information at or just before blood culture sampling was extracted from medical charts. Factors potentially predictive of bacteraemia were analysed using Fisher's exact test, followed by multivariable logistic regression model analysis. Main Results: A total of 200 patients (male: female=119:81, 64.3±19.1 years old) comprised this study; 57 (28.5%) had positive blood culture results. Multivariable logistic regression analysis revealed that age >60 years (OR=2.75, 95% CI 1.23 to 6.48, p=0.015), female sex (OR=2.21, 95% CI 1.07 to 4.67, p=0.038), pulse rate >90 bpm (OR=5.18, 95% CI 2.25 to 12.48, p<0.001) and neutrophil percentage >80% (OR=3.61, 95% CI 1.71 to 8.00, p=0.001) were independent risk factors for positive blood culture results. The area under the receiver operating characteristic curve analysis of this model was 0.796. Conclusions: Our results emphasise the importance of taking blood cultures if the pulse rate is >90 bpm, in elderly patients and in women, and for ordering a differential white cell count.